Kegiatan Gemar Baca Al-Qur’an dengan Pendekatan Aset-Based Community Development (ABCD): Upaya Mahasiswa dalam Mendorong Anak-Anak dan Remaja untuk Mencintai Al-Qur’an - M. Ali Sidik; Ahmad Habibbullah; Indri Wulan Romadhon; Ika Setia Purnama; Fauzah Bayu; Nana Hermana; Rizkia Cahya; Yohana Ersi; Ayu Ambarwati; Ibnu Hajar; Tomi Apriyadi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The Qur'an is the divine word revealed to the Prophet Muhammad through the angel Jibril as a great miracle and a guide for the lives of Muslims. Reading the Qur'an is not only a form of worship but also the foundation of Islamic education in building character and knowledge. However, in Indonesia, interest in reading the Qur'an among children and adolescents tends to be low due to the influence of technology and social media. This study aims to explore students' efforts in fostering children's and teenagers' love for the Qur'an through the Gemar Baca Al-Qur'an program. The study uses a qualitative method with participatory observation over four weeks, involving participants aged 4–15 years. The results of the study show: (1) the program increases interest in reading the Qur'an through an active and enjoyable approach, (2) sustainability is ensured through collaboration with Iremas Jami' Darussalam and DKM, (3) support from religious leaders and the community is a key factor in the program's success. It is recommended that this program be further developed to encourage the younger generation to love the Qur'an even more